An acidic phospholipase A2 with antibacterial activity from Porthidium nasutum snake venom - Vargas Muñoz, Leidy Johana (2012)
Snake venoms are complex mixtures of proteins among which both basic and acidic phospholipases A2 (PLA2s) can be found. Basic PLA2s are usually responsible for major toxic effects induced by snake venoms, while acidic PLA2s tend to have a lower toxicity. A novel PLA2, here named PnPLA2, was purified from the venom of Porthidium nasutum by means of RP-HPLC on a C18 column. PnPLA2 is an acidic protein with a pI of 4.6, which migrates as a single band under both non-reducing and reducing conditions in SDS-PAGE. PnPLA2 had a molecular mass of 15,802.6 Da, determined by ESI-MS. Three tryptic peptides of this protein were characterized by HPLC-nESI-MS/MS, and N-terminal sequencing by direct Edman degradation showing homology to other acidic PLA2s from viperid venoms. PnPLA2 displayed indirect hemolytic activity in agarose erythrocyte-egg yolk gels and bactericidal activity against Staphylococcus aureus in a dose-dependent manner, with a MIC and MBC of 32 μg/mL. In addition, PnPLA2 showed a potent inhibitory effect on platelet aggregation with doses up to 40 μg/mL. This acidic PLA2, in contrast to basic enzymes isolated from other viperid snake venoms, was not cytotoxic to murine skeletal muscle myoblasts C2C12. This is the first report on a bactericidal protein of Porthidium nasutum venom.